IMPROVING STUDENTS READING COMPREHENSION THROUGH PLAN - Susanto, Edy; ., Sofian; Marbun, Rismaya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak Penelitian ini berjudul Peningkatan Kemampuan Siswa Melalui PLAN. Tujuan dari penelitian ini adalah untuk membantu mengatasi kesulitan siswa dalam memahami teks berbentuk narrative. Subjek penelitian adalah siswa kelas XI IPS I; yang berjumlah 45 siswa. Penelitian ini dilaksanakan sebanyuak 4 siklus. Peneliti menggunakan objektif test, tabel pengamatan, dan catatan sebagai alat pengumpul data. Hasil penelitian menunjukan peningkatan pemahaman siswa didalam membaca dari siklus pertama sampai pada siklus akhir. Rata-rata nilai pencapaian siswa meningkat dari 63.70 (poor to average), siklus kedua 71.85 (average to good), tahap ketiga 78.67 (average to good) dan tahap keempat 85.78 (good to excellent). Berdasarkan hasil dari siklus pertama sampai pada siklus akhir, strategi membaca PLAN telah membantu siswa didalam memahami teks berbentuk narrative. Oleh karena itu, penulis menyimpulkan bahwa pemahaman siswa terhadap teks berbentuk narrative meningkat dengan baik dengan menerapkan strategi membaca Predict, Locate, Add and Note. Kata Kunci: PLAN, Meningkatkan, Pemahaman Membaca Abstract This research entitled Improving Students Reading Comprehension Through PLAN. The purpose of this research is to solve the students problem which was their difficulty in comprehending the narrative text. The subject of this research was class XI IPS I; which consist of 45 students. This research was done in four cycles. The researcher used objective test, observation checklist tables, and field notes as the tools of collecting data. The research finding showed that the students reading comprehension improved from the first cycle to the last cycle. The mean score of students achievementimproved from 63.70 (poor to average), the second cycle was 71.85 (average to good) the third cycle was 78.67 (average to good) and the fourth cycle was 85.78 (good to excellent). Based on the result of the first cycle up to the last cycle, PLAN reading strategy has helped students in comprehending narrative text. Therefore, the writer concludes that students reading comprehension of narrative text improved very well by applying Predict, Locate, Add, and Note reading strategy. Keywords: PLAN, Improving, Reading Comprehension